SISTEM PENDUKUNG KEPUTUSAN PENERIMA PKH MENGGUNAKAN METODE SAW - Sektio Ririn; Firliana, Rina; Andriyanto, Teguh; Sucipto, Sucipto (Universitas Islam Balitar Blitar, 2023)
The Family Hope Program is a conditional social assistance program for poor and vulnerable families and/or individuals. The current problem is that the process of determining PKH beneficiaries by PKH administrators and assistants in Bendolo Village is still done manually and has not been supported by an optimal system. Decision Support System In determining beneficiaries, there are 6 criteria used. Problems often occur in the selection of beneficiaries, one of which is the long process of determining beneficiaries and the emergence of community prejudice regarding beneficiaries of the program. The result of this study is the formation of a decision support system to determine eligible and ineligible PKH beneficiary candidates using the SAW method.